2014
DOI: 10.1007/s12152-014-9207-2
|View full text |Cite
|
Sign up to set email alerts
|

A Bio-Social and Ethical Framework for Understanding Fetal Alcohol Spectrum Disorders

Abstract: The diagnosis of Fetal Alcohol Spectrum Disorders (FASDs) is embedded in a matrix of biological, social and ethical processes, making it an important topic for crossdisciplinary social and ethical research. This article reviews different branches of research relevant to understanding how FASD is identified and defined and outlines a framework for future social and ethical research in this area. We outline the character of scientific research into FASD, epidemiological discrepancies between reported patterns of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Prevention messaging thus risks perpetuating stigma and promoting the idea that women who give birth to children with FASD are irresponsible and careless mothers who are at fault. 5,[18][19][20] The risk of perpetuating stigma is heightened when prevention messaging neglects both the factors that may lead a woman to drink while pregnant (e.g., social pressures, being unaware of or not wanting to reveal the pregnancy, coping strategies) 21 and other factors that can modulate the susceptibility to the development of an FASD (e.g., nutrition, smoking, and socio-economic effects).…”
Section: Stigma and Blame Create Barriers To Carementioning
confidence: 99%
“…Prevention messaging thus risks perpetuating stigma and promoting the idea that women who give birth to children with FASD are irresponsible and careless mothers who are at fault. 5,[18][19][20] The risk of perpetuating stigma is heightened when prevention messaging neglects both the factors that may lead a woman to drink while pregnant (e.g., social pressures, being unaware of or not wanting to reveal the pregnancy, coping strategies) 21 and other factors that can modulate the susceptibility to the development of an FASD (e.g., nutrition, smoking, and socio-economic effects).…”
Section: Stigma and Blame Create Barriers To Carementioning
confidence: 99%
“…For example, if a duty of care were to be imposed on expectant mothers, any action taken by pregnant women, irrespective of how mundane this may be, could be subject to judicial scrutiny, and it would be extremely difficult to identify the circumstances in which mothers would have breached their duty to their unborn children (Do & Mapulanga-Hulston, 2013). Meurk, Lucke and Hall (2014) have observed that there is a growing body of legal decisions arising from actions taken in attempts to impose medical treatment on pregnant women. They discuss the tendency to make pregnant women's bodies the subject of state surveillance, particularly in countries such as the United States and Finland, where women can be subject to compulsory commitment and/or incarceration if their AOD use is deemed to be potentially harmful to the foetus.…”
Section: 6 Exploring the Legal Status Of The 'Unborn Child' Versus Tmentioning
confidence: 99%
“…They discuss the tendency to make pregnant women's bodies the subject of state surveillance, particularly in countries such as the United States and Finland, where women can be subject to compulsory commitment and/or incarceration if their AOD use is deemed to be potentially harmful to the foetus. This kind of regulation of women can be seen to grant certain legal rights to foetuses, where the rights of the foetus are deemed superior to those of the mother, and the state's assumed authority to protect the foetus overrules the interests of the mother (Meurk et al, 2014). Criminalisation of maternal substance use threatens women's autonomy, and the status of women as equal citizens who are entitled to protection under the law may further jeopardise infant health and wellbeing, may lead women to avoid antenatal care, may unfairly target already-marginalised groups, and does not necessarily prevent substance abuse among women (Zizzo, Di Pietro, Green et al, 2013).…”
Section: 6 Exploring the Legal Status Of The 'Unborn Child' Versus Tmentioning
confidence: 99%
See 2 more Smart Citations